Risk factors for fatal outcome in surgical patients with postoperative aspiration pneumonia. (March 2016) - Studer, Peter; Räber, Genevieve; Ott, Daniel; Candinas, Daniel; Schnüriger, Beat
Abstract: Introduction: Aspiration pneumonia in hospitalized surgical patients has been associated with a mortality of approximately 30%. The aim of this study was to assess pre-, intra- and postoperative risk factors for mortality in patients suffering aspiration pneumonia after abdominal surgery. Methods: Retrospective study from 01/2006–12/2012 of patients with clinically and radiologically confirmed aspiration pneumonia after abdominal surgery. Results: A total of 70 patients undergoing abdominal surgery and postoperative aspiration pneumonia were identified. There were 53 (76%) male patients, the mean age was 71 ± 12 years and the mean ASA score was 3 ± 1. The surgical procedures included 32 colorectal or small bowel resections, 10 partial liver resections, 9 gastric surgeries, 8 esophageal resections, 5 pancreatic surgeries, and 6 hernia repairs. Aspiration pneumonia occurred at mean postoperative day 7 ± 10. Overall, 53% (n = 37) of patients required re-intubation, with 4 ± 5 days of additional mechanical ventilation. Mean hospital and ICU length of stay was 32 ± 25 days and 6 ± 9 days, respectively. Overall mortality was 27% (n = 19). Forward logistic regression revealed older age [OR 7.41 (95% CI: 1.29–42.62)], bilateral aspiration pneumonia [OR 7.39 (95% CI: 1.86–29.29)] and intraoperative requirement of blood component transfusion [OR 5.09 (95% CI: 1.34–19.38)] as independent risk factors for mortality (overall R 2 = 0.336). Conclusion: Postoperative aspiration pneumonia remains a severe complication with significant mortality. Increasing age, the need for intraoperative blood component transfusion and bilateral pulmonary infiltrates are independent risk factors for fatal outcome after aspiration pneumonia. Therefore, these patients suffering aspiration pneumonia require special attention and increased monitoring. Highlights: Postoperative aspiration pneumonia remains a severe disease with a significant mortality of 27% in this series. Older age, blood transfusion and bilateral pulmonary infiltrates are risk factors for mortality after aspiration pneumonia. The identification of patients at increased risk for death after aspiration may help to further improve patients outcome.